New enterant in the class of uropathogens-Shewanella algae - Ostwal, K; Shah, P; Pathak, S; Jadhav, A; Shaikh, N (Asian Journal of Medical Sciences, 2015)
A 70 year old diabetic male presented with fever, urgency of micturition, oliguria, swelling over both legs. His midstream urine sample was sent for microbiological examination and it revealed Shewanella algae. Patient was treated with antibiotics and he recovered completely after treatment. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11503 Asian Journal of Medical Sciences Vol.6(4) 2015 92-95